If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 4x + 6 = -3 Reorder the terms: 6 + 5x + 4x = -3 Combine like terms: 5x + 4x = 9x 6 + 9x = -3 Solving 6 + 9x = -3 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 9x = -3 + -6 Combine like terms: 6 + -6 = 0 0 + 9x = -3 + -6 9x = -3 + -6 Combine like terms: -3 + -6 = -9 9x = -9 Divide each side by '9'. x = -1 Simplifying x = -1
| 0.5(4z+7+6.1)=0.6(4z-4) | | 180=7x+4+5x+3+2x+5 | | 34=5x+1 | | 4y=6-2x | | 5(x-3)=5x-3 | | 400x-370x=1540 | | 400x+370x=1540 | | 60x=75x-825 | | 180=2x+x+90 | | f(x)=x+2x+15 | | (x-4)(x^2-x-20)=0 | | 60x=75x-11 | | 60x+75x=11 | | (x-4)=(3x+2) | | 6x^2-6x-18=0 | | 4.9x^2+20x+1=5 | | 80x+90x=680 | | 80x+90x=680 | | 0=5t^2+2 | | x+.05=1 | | 2.5x+4.5(462-x)=1441 | | c=jp | | 11-3m=5 | | 11-3m=6 | | 11-3m=12 | | 3x+2y+5y-4y-8x= | | 4(x+4)+6=7x-3(x-5) | | .25x+.5(63-x)=21.25 | | 13-(3+6y-2(y+5))=-5(2y-3)-(8(y-1)-11y+12) | | -2(-4x+-2x)=132 | | 11-3m=10 | | 8-y-2=5 |